A Real-time Application Framework for Web-Based Speech Recognition Using HTTP/2 and SSE - Kalamullah Ramli; Asril Jarin; Suryadi Suryadi (Institute of Advanced Engineering and Science, 2018)
The performance of network-based speech recognition application is mainly determined by the availability of all speech data received on the server and also the realtimeness in delivering the recognition results from the server. On the basis of full-duplex speech recognition application this paper proposes a real-time application framework for web speech recognition using HTTP/2 protocol and Sender-Sent Events (SSE). A number of experiments were performed to compare the latency of both the application using HTTP/2 plus SSE and the full-duplex application using WebSocket. The results showed that the proposed framework offers better alternative for a web-based speech recognition than the framework using WebSocket.